The oblique fracture of the manubrium sterni caused by a seatbelt-a rare injury? Treatment options based on the experiences gained in a level I trauma centre - Schulz-Drost, Stefan; Oppel, Pascal; Grupp, Sina; Taylor, Dominic; Krinner, Sebastian; Langenbach, Andreas; Hennig, Friedrich; Mauerer, Andreas (International Orthopaedics, 2015)
Sternal fractures are rare with 3-8 % out of the total number of trauma cases mostly caused by direct impact to the anterior chest wall. Most cases described are due to motor vehicle crash either caused by direct impact to the steering wheel or by the seat belt. Fractures mainly occur to the sternal body. Only rarely are cases of manubrium fractures described in literature, for example, in relationship with a direct impact to the shoulder which caused an oblique fracture near to the sternoclavicular joint. Three patients with profoundly dislocated oblique manubrium fracture were admitted to our Level I Trauma Center in 2012 and 2013. Those patients suffered from instability of the upper sternum and the shoulder girdle.Between January 2012 and October 2013, a total of 538 trauma patients were admitted to the emergency room and received whole body CT-scan. They were analysed retrospectively for sternal fractures. In cases of instability and dislocation, fracture stabilisation was performed by anterior plating through a medial approach using low profile titanium plates (MatrixRib®).Seventy-nine (14.7 %) patients showed sternal fracture, out of which 13 (2.4 %) patients showed a fracture of manubrium, ten caused by seatbelt. In three cases stabilization was performed. Follow up showed sufficient consolidation without complications.A total of 16.5 % of sternal fractures were localized at the manubrium, mostly caused by seat belt. Fractures without significant dislocation seemed to be stable and healed well under conservative treatment. Dislocation in this region leads to unstable shoulder girdle. Anterior plating provides sufficient stabilisation and allowed consolidation.
EVALuna2:15839